가래나무 수피의 페놀성 화합물 - 김진규; Jin Kyu Kim; 사전령; Chuan Ling Si; 배영수; Young Soo Bae (목재공학, 2006)
Juglans mandshurica barks were collected, extracted with acetone-$H_2O$ (7:3, v/v), fractionated with n -hexane, $CH_2Cl_2$, and EtOAc, and freeze dried to give some dark brown powder. The EtOA cand $H_2O$ soluble fractions were chromatographe d on a Sephadex LH-20 column using $H_2O$-MeOH and EtOH-hexane mixture as eluents. Spectrometric analysis such as NMR and MS, including TLC,were performed to characterize the structures of the isolated compounds. From the EtOAc and $H_2O$ soluble fractions, three flavanols (1~3), three flavonols (4~6) and five flavonol glycosides (7~11) were isolated and elucidated. 가래나무 수피를 채취하여 건조시킨 후 분말로 제조하고 3.2 kg을 아세톤-물(7:3, v/v) 혼합용액으로 추출하여 유기용매를 제거한 후 헥산, 메틸렌클로라이드, 에틸아세테이트 및 물을 사용하여 네 개로 분획하고 에틸아세테이트 및 수용성 분획물에 대하여 칼럼 크로마토그래피를 수행하였으며 용리용매로는 메탄올 수용액과 에탄올-헥산 혼합액을 사용하였다. 그 결과 flavanol 화합물인 pinobanksin, taxifolin 및 ampelopsin, flavonol 화합물인 kaempferol, quercetin 및 myricetin 과 flavone glycoside 화합물인 afzelin, astragalin, quercitrin, isoquercitrin 및 myricitrin을 단리하였으며 NMR 및 MS 스펙트럼을 이용하여 구조를 결정하였다.